Microsatellite genotyping and molecular screening of pea (Pisum sativum L.) germplasm with high-resolution melting analysis for resistance to powdery mildew - Ioannis Ganopoulos (2018)
© 2018 Elsevier B.V. Pea (Pisum sativum, L.) is an important legume crops in the world especially for the cool-season, used both for human food and animal feed having high protein and vitamin content. As with many crops Gene Banks hold significant collections which in many cases have not been assessed through molecular genotyping. Yet, this pre-breeding step is highly important in order to design an efficient breeding strategy in order to develop varieties of high yield and quality being at the same time resistant to pathogenes. Microsatellite markers have been developed for most of the crops and when combined with High Resolution Melting analysis (HRM) they provide a fast, accurate and efficient method for the genotyping of plant species like Pisum sativum. We have used here seven microsatellite loci coupled with HRM analysis, which proved to be efficient in order to genotype, the thirty-five accessions of the Greek Gene Bank collection. Furthermore, we were able by using a specific functional marker to characterise and group these varieties and landraces for the presence of the powdery mildew resistance gene. This is a useful method in breeding for the fast and accurate tagging offspring for the presence of the resistant gene in a molecular assisted (MAS) breeding program for the development of powdery mildew resistant varieties.